2018
DOI: 10.1088/1741-2552/aa966d
|View full text |Cite
|
Sign up to set email alerts
|

An optimized content-aware image retargeting method: toward expanding the perceived visual field of the high-density retinal prosthesis recipients

Abstract: The proposed method is beneficial to expand the perceived visual field of prosthesis recipients and improve their object detection and recognition performance. It suggests that our method may provide an effective option for image processing module in future high-density retinal implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…This fact results in loss of visual information which affects patient perception. However, there are research groups using computer vision approaches to try to expand the perceptible visual field in implanted patients to provide useful information in the peripheral vision [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…This fact results in loss of visual information which affects patient perception. However, there are research groups using computer vision approaches to try to expand the perceptible visual field in implanted patients to provide useful information in the peripheral vision [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that object borders were available for recipients to recognize objects under prosthesis vision 16,27,28,29 . For extracting the robust edge information, we employed the guided filter algorithm in this study, whose main advantages were manifested in denoising and maintaining edge information 26 …”
Section: Methodsmentioning
confidence: 99%
“…It can be observed that object borders were available for recipients to recognize objects under prosthesis vision. 16,27,28,29 For extracting the robust edge information, we employed the guided filter algorithm in this study, whose main advantages were manifested in denoising and maintaining edge information. 26 Similar to the general filtering process, an output image q can be obtained by operating an input image p with a filter kernel W. Differently, in the guided filtering process, the filter kernel function W is associated with a guidance image I, which guides the output image q to keep consistent texture with it.…”
Section: Guided Filtermentioning
confidence: 99%
See 2 more Smart Citations